Vulnerability as a (pre) political category. Reading notes on «Essere morti insieme. L’evento dell’11 settembre 2001» by Mauro Carbone - Palazzo, Sandro (Governare la paura. Journal of interdisciplinary studies, 2008)
The essay considers Mauro Carbone’s reflection on the meaning of 9/11 2001 as far as the relationship between philosophy and politics is concerned. Particular attention is devoted to the concept of vulnerability, thought as the most relevant philosophical heritage left by the Twin Towers attack to contemporary culture.